Class and Precarity: An Unhappy Coupling in China's Working Class Formation. (June 2018) - Smith, Chris; Pun, Ngai
In refuting Guy Standing's precariat as a class, we highlight that employment situation, worker identity and legal rights are mistakenly taken as theoretical components of class formation. Returning to theories of class we use Dahrendorf's reading of Marx where three components of classes, the objective, the subjective and political struggle, are used to define the current formation of the working class in China. Class is not defined by status, identity or legal rights, but location in the sphere of production embedded within conflictual capital–labour relations. By engaging with the heated debates on the rise of a new working class in China, we argue that the blending of employment situation and rights in the West with the idea of precarity of migrant workers in China is misleading. Deconstructing the relationship between class and precarity, what we see as an unhappy coupling, is central to the article.